Seismic behaviour of single storey rat-trap bond masonry buildings retrofitted with GFRP - Sivaraja, S. Saileysh; Thandavamoorthy, T.S. (Journal of Structural Engineering, 2024)
The paper presents in detail the experimental and numerical investigation using ANSYS on 1/3 model of a Rat-trap building of size 2.10 m × 1.10 m with thickness of the wall of 92 mm with and without roof slab under base impact test using a shock table especially designed and fabricated for this purpose. One building was tested without a roof slab and the other was provided with a reinforced concrete roof slab consisting of weld mesh made of 3 mm mild steel rod spaced at 50 mm both ways. For each impact its velocity was calculated from the height of fall from which the energy imparted to the building was calculated. The energy absorbed by the building without roof slab was 3600 Nm after 24 impacts and that with roof slab was 4100 Nm after 21 impacts. The corresponding values for the model repaired with GFRP wrapping was 7363.71 Nm after 32 impacts. Pertinent conclusions drawn from the experimental and numerical investigations are also discussed. These conclusions have practical bearings in the construction of Rat-trap bond masonry.